(untitled) (Annals of Bangladesh Agriculture, 2024)
Many field crop lands are being transformed to fruit orchards in different locations of Bangladesh. There is an ample scope to cultivate intercrops in the orchards following scientific manner and proper technology including suitable varieties. In this study, mango and orange orchards were transformed to agroforestry system in Kotchandpur upazila under Jhenaidah district to investigate the performances of selected vegetable varieties (bottle gourd, stem amaranth, papaya, cauliflower, and country bean) developed by the Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU). Randomized complete block design was used to compare agroforestry (mango and orange orchards) and non-agroforestry (open field) treatments for identifying suitable tree-vegetable combinations. The results indicated that yields of the tested vegetables were higher in the non-agroforestry system (crop field without trees) compared to the agroforestry system. Yields of bottle gourd stem amaranth, cauliflower, and country bean in agroforestry systems decreased by 21, 7, 18, and 19%, respectively, compared to non-agroforestry system. On the contrary, yield reductions were 7.9, 15.7, 3.9 and 4.6% in mango-based agroforestry than orange-based agroforestry for bottle gourd, stem amaranth, cauliflower, and country bean, respectively. The findings suggested that although all the tested vegetables can be grown in agroforestry, but creeping type vegetables are less suitable. Despite the observed reduction in yields, the fruit tree-based agroforestry system demonstrated its potential as a viable alternative, offering to reduce crop failure risk to the farmers and optimizing land utilization. The order of the suitability of the tested vegetables are stem amaranth > cauliflower > country bean > bottle gourd in agroforestry systems. Ann. Bangladesh Agric. 27(2):191-199